(untitled) (International Journal of Engineering and Computer Science, 2025)
The rapid adoption of cloud-optimized data engineering systems has revolutionized the way organizations handle vast volumes of data. These systems offer unmatched scalability, flexibility, and cost-efficiency. However, their increasing complexity and reliance on distributed architectures have made them susceptible to a wide range of faults, such as hardware failures, software bugs, and network disruptions. Faults in cloud environments can lead to severe consequences, including service outages, compromised data integrity, and increased operational costs. Artificial intelligence (AI) has emerged as a transformative solution for addressing these challenges. By leveraging advanced algorithms and computational power, AI facilitates real-time fault detection, predictive maintenance, and automated remediation. Machine learning (ML) and deep learning (DL) models analyze large-scale system logs, metrics, and telemetry data to identify anomalies, predict potential faults, and recommend or execute corrective actions before failures occur. These capabilities enhance system reliability, minimize downtime, and optimize resource utilization. This article provides an in-depth exploration of AI-driven fault detection in cloud-based environments, covering foundational methodologies, cutting-edge algorithms, and practical applications. Key focus areas include AI frameworks for anomaly detection, predictive analytics, and self-healing mechanisms integrated into leading cloud platforms such as Amazon Web Services (AWS), Google Cloud Platform (GCP), and Microsoft Azure. Real-world case studies illustrate how AI transform’s fault management by reducing mean time to resolution (MTTR) and preventing cascading failures. Despite its transformative potential, implementing AI-based fault detection presents challenges. Issues such as data sparsity, imbalanced fault datasets, computational demands, and ethical concerns, including biases and false positives, complicate deployment. Moreover, the dynamic nature of cloud systems requires continuous learning and adaptation to evolving fault patterns. Looking ahead, this article identifies emerging trends and innovations in AI for fault detection. These include the integration of edge AI with cloud systems, advances in explainable AI to build trust in automated decision-making, and the rise of autonomous systems capable of self-diagnosis and self-healing. As organizations increasingly rely on cloud infrastructures, the synergy between AI and fault detection will play a critical role in shaping the resilience and efficiency of next-generation data engineering systems.